2017
DOI: 10.5604/01.3001.0010.0289
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Intrapulmonary Vascular Dilatations and the Risk of Developing Hepatopulmonary Syndrome in Liver Transplant Candidates

Abstract: Patients with IPVD appear to have a substantial risk of developing oxygenation impairment over time and progress to HPS. In our cohort, survival in patients with HPS and isolated IPVD is not different when compared to those without IPVDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
6
0
8
Order By: Relevance
“…7,15 IPVD is also deemed to be an essential criterion for the diagnosis of HPS, while most of the researchers considered that there was no need to screen IPVD patients with normal oxygenation from cirrhotic patients in the past. However, Manual et al 16 found that approximately 35% of IPVD patients with normal gas exchange developed HPS by serial ABG measurement. IPVD-only patients were found to be in a hyperdynamic state, presenting as a higher cardiac output, cardiac index, and left ventricular stroke volume, leading to higher risk of dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…7,15 IPVD is also deemed to be an essential criterion for the diagnosis of HPS, while most of the researchers considered that there was no need to screen IPVD patients with normal oxygenation from cirrhotic patients in the past. However, Manual et al 16 found that approximately 35% of IPVD patients with normal gas exchange developed HPS by serial ABG measurement. IPVD-only patients were found to be in a hyperdynamic state, presenting as a higher cardiac output, cardiac index, and left ventricular stroke volume, leading to higher risk of dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Mendizabal et al, 2017 (11) a sobrevida em 5 anos dos pacientes com SHP que não são submetidos a transplante hepático é de 23%, enquanto a dos pacientes sem SHP chega a 63% no mesmo período. Ao se analisarem os pacientes submetidos a transplante hepático a sobrevida foi similar entre portadores e não portadores de SHP.…”
Section: Prognósticounclassified
“…Estudo recente que gerou grande interesse na comunidade mundial foi realizado pelo grupo de Mendizabal et al, 2017 (11) , e analisou 20 pacientes cirróticos assintomáticos. Todos foram submetidos à oximetria de pulso e a gasometria arterial para cálculo do gradiente AaO 2 .…”
Section: Critérios Diagnósticos De Shpunclassified
See 1 more Smart Citation
“…The presence of IVPDs is essential for the diagnosis of HPS, and if many IVPDs are present in POPH, it worsens transplant outcomes. 69…”
Section: Introductionmentioning
confidence: 99%